EPIDEMIOLOGICAL ANALYSIS OF SCHISTOSOMIASIS IN THE MUNICIPALITY OF EUNÁPOLIS (BA): A DESCRIPTIVE STUDY BASED ON SURVEILLANCE DATA FROM 2017 TO 2022 - de Lima, Diana; Almeida da Silva, Flaelma; Henrique Paiva Mezete, Kaio; Rita Kirmse Pereira, Adma; Walter Lima Monteiro, Ronnie (Health and Society, 2025)
Schistosomiasis is a parasitic endemic disease caused by the helminth Schistosoma mansoni, whose transmission cycle involves humans as the definitive host and snails of the Biomphalaria genus as intermediate hosts. In Brazil, its persistence is directly linked to poor sanitation and frequent exposure to contaminated freshwater bodies, especially in socioeconomically vulnerable regions. This study aimed to characterize the epidemiological profile of schistosomiasis in the municipality of Eunápolis, Bahia, from 2017 to 2021, in order to support targeted surveillance and control strategies. This is a descriptive, quantitative, and cross-sectional research based on secondary data from the Notifiable Diseases Information System (SINAN) and the Schistosomiasis Control Program (PCE). Data were analyzed using Microsoft Excel spreadsheets, with calculations of prevalence, incidence, and relative frequency. A total of 113 confirmed cases of schistosomiasis were recorded during the study period, predominantly among males (54.9%) aged between 30 and 59 years. The years 2017 and 2018 showed the highest number of cases, followed by a declining trend in subsequent years. The neighborhoods with the highest relative frequencies were Pequi, Juca Rosa, and Alecrim II. The findings highlight the continued active transmission of schistosomiasis in the municipality, associated with structural factors such as lack of basic sanitation and occupational or recreational exposure to contaminated aquatic environments, emphasizing the need for active surveillance, health education, and intersectoral vector control actions.